(3efThQ Edi Bd YHO Gddg hBd SdjeGfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdefRg Yf GdacQ hGdJMOjO hJhSdJ Edjg HGdEeGe GdbGFe HGdhYO hGdhYjO ef GdYHO GdebJfi GdfGUM dLejY Cgd GdJhMjO hGdEjeGf s
(3BNQgG (B:s
(3hQO Edjg cJGH Scjf HNW jOGg jPcQ ajg hbO LYdJ dc GdfXQ ai LejY GdCedGc GdeSJLjjf heWGdHI ef Ydjg Ojf hGbJVGg JeJ hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B97s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis